Nuclear disasters and health: lessons learned, challenges, and proposals - Ohtsuru, Akira; Tanigawa, Koichi; Kumagai, Atsushi; Niwa, Ohtsura; Takamura, Noboru; Midorikawa, Sanae; Nollet, Kenneth; Yamashita, Shunichi; Ohto, Hitoshi; Chhem, Rethy K; Clarke, Mike (The Lancet (British edition), 2015)
Past nuclear disasters, such as the atomic bombings in 1945 and major accidents at nuclear power plants, have highlighted similarities in potential public health effects of radiation in both circumstances, including health issues unrelated to radiation exposure. Although the rarity of nuclear disasters limits opportunities to undertake rigorous research of evidence-based interventions and strategies, identification of lessons learned and development of an effective plan to protect the public, minimise negative effects, and protect emergency workers from exposure to high-dose radiation is important. Additionally, research is needed to help decision makers to avoid premature deaths among patients already in hospitals and other vulnerable groups during evacuation. Since nuclear disasters can affect hundreds of thousands of people, a substantial number of people are at risk of physical and mental harm in each disaster. During the recovery period after a nuclear disaster, physicians might need to screen for psychological burdens and provide general physical and mental health care for many affected residents who might experience long-term displacement. Reliable communication of personalised risks has emerged as a challenge for health-care professionals beyond the need to explain radiation protection. To overcome difficulties of risk communication and provide decision aids to protect workers, vulnerable people, and residents after a nuclear disaster, physicians should receive training in nuclear disaster response. This training should include evidence-based interventions, support decisions to balance potential harms and benefits, and take account of scientific uncertainty in provision of community health care. An open and joint learning process is essential to prepare for, and minimise the effects of, future nuclear disasters.